Grammatical Error Analysis of College Students’ Essay of the University of Saint Anthony - Bagacina, Cris S. (Universitas Muhammadiyah Lampung, 2024)
Writing proficiency is a fundamental language skill crucial for ESL students. To achieve this, they should acquaint themselves with the fundamentals of grammar to produce well-written essays. The grammatical accuracy of written compositions contribute to the comprehensibility of the ideas presented by students. Therefore, language teachers are expected to teach and provide them with sufficient lessons and exercises related to writing. This study aimed to identify and analyze the committed grammatical errors of students in their essays. Fifteen essays from students enrolled in the College of Liberal Arts at the University of Saint Anthony were the focus of this study. The research methods employed in this study are quantitative and qualitative research methods. To identify the grammatical errors committed by the students, error analysis was employed. The results revealed that the top errors identified in the essays were related to capitalization, punctuation, word selection, verbs, pronouns, and sentence structure while the common characteristics of the errors made by the students were omission and misformation. The findings of this study suggest that ESL teachers can use the identified errors to help students improve their